Determinants of Internal Medicine Outpatient Service Utilization at Klinik Utama Kasehat Walafiat, Aceh Besar, Indonesia: A Cross-Sectional Study - Maulafi Alhamdi Stivani; Rachmad Suhanda; Nurjannah Nurjannah (Heca Sentra Analitika, 2026)
Utilization of specialist outpatient services is an important indicator of healthcare access and health-seeking behavior. Despite the availability of Internal Medicine Specialist outpatient services at Kasehat Walafiat Primary Clinic, service utilization remains suboptimal. Understanding the factors associated with healthcare utilization is essential for improving access and service planning. This study aimed to examine the associations of health beliefs regarding specialist services, enabling access factors, and healthcare need factors with the utilization of Internal Medicine Specialist outpatient services at Kasehat Walafiat Primary Clinic, Aceh Besar, Indonesia. A quantitative cross-sectional study was conducted among adults residing within the clinic’s service area. Data were collected using a validated and reliable structured questionnaire and analyzed using descriptive statistics and binary logistic regression. The findings showed that health beliefs regarding specialist services, enabling access factors, and healthcare need factors were significantly associated with the utilization of Internal Medicine Specialist outpatient services. Among the study variables, healthcare need factors demonstrated the strongest association with service utilization. These findings suggest that the utilization of specialist outpatient services is influenced by individual perceptions of specialist care, access-related conditions, and perceived healthcare needs. Efforts to improve specialist outpatient service utilization should focus on strengthening community health education, improving access to healthcare services, simplifying service procedures, and promoting the early detection and continuous management of chronic health conditions.